A13 Phenotyping neural networks in an ovine model of huntington's disease. (29th August 2012) - Perentos, N; Watson, T; Jones, M; Morton, J
Abstract : A large animal transgenic model of Huntington's disease (HD) has been recently developed in domestic sheep (Ovis aries L). 1 Sheep are a long-lived species with large brains, complex basal ganglia and convoluted neocortex; compared to standard models in short-lived rodents with lissencephalic cortices, this ovine model may therefore be better-suited for electrophysiological characterisations of early disease stages and for the development of novel treatments. Using a sheep model will also reduce costs relative to non-human primates, and enables large-scale, long-term and multi-site electrophysiological recording during behavioural testing paradigms. 2 Sleep is an essential and ubiquitous brain state that is known to deteriorate in humans suffering from HD. As a first step towards assessing the normal electrophysiological features of sheep, we aimed to characterise sleep architecture using electroencephalography in healthy sheep. In addition we performed some common behavioural manipulations known to modulate sleep architecture. These include sleep deprivation and learning prior to sleep. The method can be expanded to generate sensitive biomarkers of intra-cortical network activity and interactions between brain structures in the behaving animal. If deterioration of these network interactions precedes the appearance of overt symptoms, this could then be targeted for treatments that might delay symptom onset. We also present deep brain recordings (of local field potentials and single neuron spike activity) from an anaesthetised animal as a proof of concept. Sheep disease models offer unique opportunities for long term in vivo electrophysiological testing, with the potential lead to novel therapeutic treatments targeting early stages of HD progression. References: 1. Jacobsen, et al. Hum Mol Genet 2010;19 :1873–82. 2. Morton AJ, Avanzo L. Executive decision-making in the domestic sheep. PLoS One 2011;6 :e15752.